How to mitigate the inhibitory effect of organizational inertia on corporate digital entrepreneurship? - Li, Wei; Chen, Wei; Pang, Qingdan; Song, Jianmin (Frontiers in Psychology, 2023)
As a novel way for incumbent firms to discover and utilize entrepreneurial opportunities in the digital era, corporate digital entrepreneurship (CDE) is significant for realizing digital transformation through dealing with organizational sclerosis and bureaucratization. Previous studies have identified the variables having positive effects on CDE and put forward practical solutions to promoting CDE. However, the majority of them have ignored the variables having negative effects on CDE and how to mitigate the inhibitory effects. In order to fill the research gap, this study investigates the causal relationship between organizational inertia (OI) and CDE and examines the moderating roles of internal factors such as digital capability (DC) and entrepreneurial culture (EC) as well as external factors such as institutional support (IS) and strategic alliance (SA). Based on multiple linear regression (symmetric) and fuzzy-set qualitative comparative analysis (asymmetric) using survey data from 349 Chinese firms, the results demonstrate that OI has a significant negative effect on CDE. In addition, DC, EC, and SA play negative moderating roles in the relationship between OI and CDE, which means that they could reduce the inhibitory effect derived from OI when incumbent firms implement CDE. Moreover, dividing OI into three dimensions discovers that the moderating roles of DC, EC, and SA present different features. This study enriches the literature on corporate entrepreneurship and provides valuable practical implications for incumbent firms to achieve successful CDE by revealing how to overcome the inertia deeply embedded in organizations.